2012
DOI: 10.2147/rrtm.s27395
|View full text |Cite
|
Sign up to set email alerts
|

Current approaches and future directions in the treatment of leprosy

Abstract: This review surveys current treatments and future treatment trends in leprosy from a clinical perspective. The World Health Organization provides a multidrug treatment regimen that targets the bacillus which causes leprosy. Several investigational drugs are available for the treatment of drug-resistant. Future directions in leprosy treatment will focus on: the molecular signaling mechanism uses to avoid triggering an immune response; prospective studies of the side effects experienced during multiple-drug ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…One alternative regimen recommended by WHO since 1998 is the provision of single dose combination of rifampicine (600 mg), ofloxacine (400 mg), and minocycline (100 mg) (ROM)for PB type leprosy patients with single lesion [7,8]. A study in Brazil also found that patients treated with MDT MB compared to ROM for 24 months showed the same results in terms of reductions in Bacterial Index (BI), and improvement in clinical and histopathological features [9].…”
Section: Introductionmentioning
confidence: 99%
“…One alternative regimen recommended by WHO since 1998 is the provision of single dose combination of rifampicine (600 mg), ofloxacine (400 mg), and minocycline (100 mg) (ROM)for PB type leprosy patients with single lesion [7,8]. A study in Brazil also found that patients treated with MDT MB compared to ROM for 24 months showed the same results in terms of reductions in Bacterial Index (BI), and improvement in clinical and histopathological features [9].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, diagnosis of leprosy can be made by finding one of the three cardinal signs of leprosy: loss of sensation in a hypopigmented or erythematous skin lession; thickening or enlargement of the peripheral nerve accompanied by loss of sensation and/ or muscle weakness in the affected nerve; or positive slit skin smear (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative regimen recommended by the WHO is a single dose of rifampicin (600 mg), ofloxacin (400 mg), and minocycline (100 mg) (ROM) for PB leprosy patients with single lesion (2). Ofloxacin and minocycline are significantly more potent than dapsone and clofazimine against M. leprae and when combined with rifampicin provide a potent bactericidal activity that could kill 98% M. leprae in the first administration (7).…”
mentioning
confidence: 99%
“…Leprosy reaction is caused by patient's immunological dynamic response to M. leprae which could happen before, during, and after MDT administration. 2 This reaction is an acute episode of the disease with constitutional symptoms, activation, sometimes accompanied with new skin efflorescence. Two types of leprosy reaction are type 1, known as reversal reaction (RR), caused by acute changes in cellu lar immun ity, and type 2 reaction known as eritema nodosum leprosum (ENL), caused by humoral immun ity process.…”
Section: Introductionmentioning
confidence: 99%